Determinants of strategic management accounting implementation in Higher Education Institutions (HEIs) in Indonesia - Evi Marlina; Adriyanti Agustina Putri; Linda Hetri Suriyanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2023)
Research aims: This study aims to examine determinants of strategic management accounting implementation, including market orientation, top management characteristics, strategy, and information technology.Design/Methodology/Approach: This research was conducted in higher education institutions (HEIs) in some areas, covering Sumatra, Java, Bali, Nusa Tenggara, Kalimantan, Sulawesi, and Papua. The research respondents were 368 HEIs leaders. Data were obtained by distributing questionnaires, and the hypotheses were tested using the partial least squares method.Research findings: The results revealed that market orientation, top management characteristics, HEIs strategy, and information technology positively affected strategic management accounting implementation.Theoretical contribution/ Originality: This research contributes to determining contingency variables in implementing strategic management accounting in HEIs.